From diagnosis to recovery – a detailed case report on a nail bed glomus tumor - Shaafie, Harris I. (Publishing Office of the University of Rzeszow, 2024)
Introduction and aim. Glomus tumors represent benign neoplastic proliferations of the glomus body, an integral thermoregulatory component within the cutaneous microvasculature. Although they can manifest at various anatomical sites, they are predominantly observed in the subungual region. The tumors present as painful, firm, purplish, solitary nodules of the extremities, especially in the nail bed. They may be solitary or multiple; solitary lesions are encapsulated and most commonly subungual, while multiple tumors are unencapsulated and rarely subungual. Description of the case. Here, we present a case of multiple glomus tumors of the right hand in an 18-year-old female who presented with complaints of painful bluish discoloration of the right little finger for six years and progressive asymptomatic nodules on the right index finger for six months. A clinical examination revealed acute tenderness in both fingers. Love’s pin test and Hildreth’s test were positive. Excision of all lesions was done and sent for histopathology, which confirmed the diagnosis. The patient was symptom-free immediately following surgery. No nail deformities were noticed, and there was no recurrence of symptoms after one year of follow-up. Conclusion. The transungual approach is a safe and effective minimally invasive surgical technique for the treatment of symptomatic nail bed glomus tumors. It offers high success rates, promising cosmetic outcomes, and minimal complications. However, careful patient selection and meticulous surgical technique are essential to avoid potential nail deformities.
Keywords: glomus tumor; subungual; transungual nail excision